VALUE CHAIN STUDY OF PAPUA NUTMEG IN FAKFAK DISTRICT - Gusti Randy Pratama; Ali Musa Harahap; Tjahja Muhandri (Agroindustrial Technology Journal, 2019)
Nutmeg is the main commodity at the Fakfak district of Papua in the agriculture subsector. Yet, the farmers have not been able to enjoy optimal added value from production results. Some of the problems included are pricing, developing derivative products and market access. The purpose of this study is to map the nutmeg value chain in the Fakfak district by understanding the characteristics of actors influencing the chain and the potential for its development. This study uses a qualitative approach with the main instrument of interviews used in data collection techniques. The results showed that actors involved in the nutmeg value chain are seed suppliers, farmers, local collectors, BUMKAM (village enterprise), IRT (home industry), inter-island traders and cooperatives. The use of nutmeg meat has become a potential in increasing the added value of processed nutmeg products in Fakfak District.